A strategic plan for Bethel UCCP Learning Center, Inc. - Datu, Arlene C.; Gomez, Aurelia Luzviminda V.; Concepcion, Sylvia B. (Davao City School of Management, University of the Philippines Mindanao, 2008)
The Bethel UCCP Learning Center (Bethel) is a non-stock and non-profit educational organization in Tagum City. For the past two years, the school exhibited a positive profit margin and good financial position. Moreover, Bethel is deemed as both internally strong and responsive to its external environment, albeit, only with a slim margin. The organization's strategic goals, which were derived from the strategic issues of the firm, were identified as follows: Focus, Cost Leadership, Differentiation and Customer Relations. Primarily, these strategies were pursued to attain the school's vision of providing well-rounded development of the students; build customer-focused relationships, trust and loyalty with its students, parents, teachers and staff, as well as sustainable profitability. The strategic planning framework of Robbins and Coulter (1999) which focused on the analyses of the firm's internal and external environment was employed in drafting this strategic plan for Bethel. Moreover, the internal strengths and weaknesses as well as its opportunities and threats were analyzed using data gathered through interviews with company stakeholders, review of internal documents, as well as information obtained from other available secondary sources. The analyses revealed that the internal strengths of Bethe are: 1) It has already established a name in industry; 2) Competent and qualified teaching staff; 3) Growing number of enrollees at the elementary level; 4) supportive School Board; 5) Accessibility/strategically located within the area identified as ?school zone,? and 6) good financial position. Among its internal weaknesses are : 1) Limited area/space for lateral expansion; 2) High turn-over of human resources; 3) Non imposition of wearing of official school uniform; and 4)Limited participation to interschool competitions. On the other hand, its opportunities are: 1) Increasing economic activities and opportunities in the City; 2) Supportive local government unit to education programs and activities; 3) Increasing population on target market (age group 5-9 years old); and 4) presence of financial institutions. For its threats: 1) Strong rivalry among competitors especially at the preschool level; and, 2) Scholarship grants by LGU. Porter's three generic strategies: cost leadership, differentiation and focus strategies provided a framework for analysis for Bethel?s strategies. A fourth generic strategy, building relationships was supplemented to further tailor-fit the broad strategies for Bethel. A total of eight alternative or support strategies were identified from which, three strategies emerged as most attractive based on the QSPM tool. These strategies are: 1) Product Development and Innovation; 2) Product Quality Monitoring; and 3) Upgrading Marketing Efforts. To ensure the proper implementation of the formulated strategies, a five-year plan and control systems are presented. The writer hopes that the findings of this strategic paper be of use to the subject company, future researchers, as well as the academe.
Thesis (Master in Management)--University of the Philippines Mindanao, December 2008.